A multicenter randomized trials to compare the bioequivalence and safety of a generic doxorubicin hydrochloride liposome injection with Caelyx ® in advanced breast cancer - Li, Yinjuan; Qi, Lu; Wang, Yu; Li, Yan; Lei, Chunpu; Zhang, Yingjuan; Cheng, Xiaoqiang; Liu, Ju; Bai, HaiHong; Zhao, Xia; Lv, Shuzhen; Xiong, Bingjun; et al. (Frontiers in Oncology, 2022)
Purpose To compare the pharmacokinetic (PK) bioequivalence (BE) and safety of a generic pegylated liposomal doxorubicin (PLD) formulation with the reference product Caelyx®. Methods A multicenter, single-dose, open-label, randomized, two-way crossover study was conducted in patients with breast cancer. For each period, the patients were administered with the test or the reference PLD intravenously at a dose of 50 mg/m2. Cmax, AUC0−t and AUC0−∞ for free, and encapsulated doxorubicin (doxorubicin) and partial AUC (AUC0−48h, AUC48h−t) for encapsulated doxorubicin were evaluated in 17 blood samples taken predose, and increasing time intervals over the following 14 days in each period. A washout period of 28-35 days was observed before crossing over. Results 48 patients were enrolled and randomised, of which 44 were included and analysed in bioequivalence set (BES). The 90% confidence intervals (CIs) of the geometric mean ratio (GMR) of Cmax, AUC0−t and AUC0−∞ for free doxorubicin and encapsulated doxorubicin all fall within the bioequivalent range of 80% to 125%. The 90% CIs of GMR of partial AUC (AUC0−48h, AUC48h−t) for encapsulated doxorubicin also fall within the bioequivalent range. 48 patients were all included in the safety set (SS). The incidence of treatment-emergent adverse events (TEAEs) related to T and R was 95.8% (46/48) and 97.8% (45/46) respectively. The highest incidence of TEAEs was various laboratory abnormalities. 2 patients withdrew due to T-drug-related AEs. Only one patient experienced serious adverse events and no death occurred in this study. There were no significant differences between the safety profiles of the generic formulation and Caelyx®. Conclusions Bioequivalence between the test and the reference products was established for free and encapsulated doxorubicin. Clinical trial registration http://www.chinadrugtrials.org.cn, identifier [CTR20210375].